The Effect of POGIL Model With PAVES-PEPS Strategy to Improve Students' Self-Efficacy and Learning Outcomes in Physics Learning - Naba Oreola Anidhea; Suliyanah Suliyanah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Learning outcomes are measures of student results achieved during the learning process. Student learning outcomes are not only influenced by cognitive aspects but also affective aspects, one of which is self-efficacy beliefs. This study aims to determine and describe the effect of applying the POGIL model with the PAVES-PEPS strategy to improve students' self-efficacy beliefs and learning outcomes in physics learning. This study used pre-experimental methods with a One-Group Pretest-Posttest Design research design. The Sample was students of XI MIPA 1 SMA Islam Sidoarjo, selected through the purposive sampling techniques. The instruments used include a self-efficacy questionnaire sheet, questions on learning outcomes, and student response questionnaire sheets to the applied learning model. The results showed a significant difference between students' self-efficacy beliefs and student learning outcomes before and after applying the learning model used. The average value of students' self-efficacy beliefs and learning outcomes has improved. They improved students' self-efficacy beliefs in the medium category and student learning outcomes in the high category. Thus, learning physics using this models affect to improve students' self-efficacy beliefs and learning outcomes.